Effect of in vitro cold storage on surviving and proliferation of cork-oak (Quercus suber L.) cultures - Romano, A; Noronha, C; Martins-Loução, M a (Congreso Forestal Español, 14 e 18 Junho de 1993, Lourizán, 1993)
Cork-oak cultures were stored in vitro without na intervening subculture, at 5º C in the dark for 5 months without loosing their capacity to regenerate when subcultured under standard conditions. The viability, proliferation rate and elongation of the explants were evaluated during 5 months of storage. Proliferation rate of stored cultures was observed during 5 months of storage. Proliferation rate of stored cultures was observed during the following 3 profileration cycles and compared to unstored controls of the same age. Shoot cultures survived with 100% viability and the proliferation rate was not statistically different from the controls. The results here described indicate the feasibility of establishing na in vitro active gene bank for Quercus suber.
Keywords: Cold storage; cork-oak; Germplasm; Medium-term storage; micropropagation; Quercus suber L.

Influence of Growth Regulators on Shoot Proliferation in Quercus suber L. - Romano, A; Noronha, C; Martins-Loução, M a (Annals of Botany, 1992)
Procedures have been developed to standardize the multiplication stage during mature cork-oak (Quercus suber L.) micropropagation. Axillary and terminal buds were established on Gresshoff and Doy basal medium containing 1 mg I−1 of 6-benzylaminopurine (BAP). Initiation of cultures was possible all over the year. The effects of BAP, Z, IBA, 1AA and NAA and various nutrient formulae on shoot growth and proliferation was investigated. BAP was more suitable than zeatin. Shoot proliferation and elongation were strongly improved by the combination BAP/IAA in the presence of low salt media, like Gresshoff and Doy or Woody Plant medium. Both rates were significantly increased when a double-phase culture system was used. Shoots have been multiplied for 1 year at the rate of three to four-fold every 4 weeks without any decline of vigour. Rooting was achieved by briefly dipping the basal ends of in vitro regenerated shoots in an IBA concentrated solution. The results here reported constitute a promising step towards large scale in vitro propagation of a species in which conventional vegetative propagation by cuttings is very difficult.
Keywords: Auxins; browning; cork-oak; cytokinins; Forestry; multiplication; Quercus suber L.; re-invigoration; re-multiplication; two-phase medium

Micropropagation of mature cork-oak (Querqus suber L.): establishment problems - Romano, A; Martins-Loução, M a (Scientia gerundensis, 1992)
Procedures have been developed to standardize the establishment stage during mature cork-oak (Quercus suber L.) micropropagation. Axillary and terminal buds cultured in Gresshof and Doy (1972) (GD) medium were used as first explant. Establishment of cultures was very difficult due to browning of the tissue and/or the medium and bacterial contamination. Browning problems, probably due to phenolic compounds exudation of the primary explant, were found to be higher in winter. Nevertheless, initiation of cultures was possible all over the year, presumably due to the preconditioning of cuttings. Explants were established in a GD medium containing 6-benzlaminopurine (BAP) 1 mgl-1. Every 4 weeks the cultures were subcultured to the same GD medium and induced to proliferate being 4:1 the multiplication rate. Shoots were induced to elongate by decreasing BAP concentration. In vitro rooting on agar-solidified medium suplemented with 1 mgl-1 indolacetic acid (IAA) gave the best results. Liquid medium (sorbarod system) and in vivo rooting were also assayed.
Keywords: browning; contaminants; cork-oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture